(untitled) - Avery, Peter (Oxford, 1992)
This introduction to the pronunciation of American English describes the sound system, suggests ways of tackling pronunciation problems, and provides a variety of techniques and exercises for use in the classroom.
Keywords: English language,English language,English language; Pronunciation,Study and teaching,Pronunciation by foreign speakers,Study and teaching,Foreign speakers